Basic mathematical skills with geometry - Hutchison, Donald (McGraw - Hill, 2005)
Maintaining its hallmark features of carefully detailed explanations and accessible pedagogy, this edition also addresses the AMATYC and NCTM Standards. In addition to the changes incorporated into the text, a new integrated video series and multimedia tutorial program are also available. Designed for a one-semester basic math course, this successful worktext is appropriate for lecture, learning center, laboratory, or self-paced courses. The book and the publisher's MathZone show a nice attempt at integrating the power of the Internet with a traditional maths text. The material is for high school readers. You can of course treat the book just as a conventional text, and refrain from accessing MathZone. In this respect, the book is well polished, being in its 6th edition, and very logically internally consistent. As befits Euclidean geometry.